Sepsis: deriving biological meaning and clinical applications from high-dimensional data - Schuurman, Alex R.; Reijnders, Tom D. Y.; Kullberg, Robert F. J.; Butler, Joe M.; van der Poll, Tom; Wiersinga, W. Joost (Intensive care medicine experimental, 2021)
The pathophysiology of sepsis is multi-facetted and highly complex. As sepsis is a leading cause of global mortality that still lacks targeted therapies, increased understanding of its pathogenesis is vital for improving clinical care and outcomes. An increasing number of investigations seeks to unravel the complexity of sepsis through high-dimensional data analysis, enabled by advances in -omics technologies. Here, we summarize progress in the following major -omics fields: genomics, epigenomics, transcriptomics, proteomics, lipidomics, and microbiomics. We describe what these fields can teach us about sepsis, and highlight current trends and future challenges. Finally, we focus on multi-omics integration, and discuss the challenges in deriving biological meaning and clinical applications from these types of data.